Le film est déjà commencé? - Lemaître, Maurice (Re:voir, 2019)
One of the founding works of letterist cinema, "Le film est déjà commencé?" (Has the Feature Started Yet?) became a major event during its first screenings in Paris in 1951. Despite the critics' lack of consideration, this film's undeniable influence - direct or hidden - on the New Wave as much as on today's cinema makes it a landmark in film history. [Cover]